Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2025)
Table of Content: 1. The Impact of Governance Application on Achieving Strategic Objectives: A Case Study of Profitable Organizations in the Kingdom for the Year 2023-2024 Dr. Hanan Abdullah Natheer, Dr. Ahmad Abdulaziz Al-Tuwayjiri 2. The impact of smart applications on the performance of the operational manager in the retail sector in some of the major private retail sectors in Jordan and Saudi Arabia for the year 2024 Mr. Mutaz Muaz (Mohammed Hafez) Muaz 3. The role of strategic analysis in improving Hajj companies’ services: An applied study on Hajj service companies in Makkah Dr. Ahmed Adel Saqqat 4. Licensure’s - Master’s – PhD system in the formation system in Nursing Professions and Health Techniques In the Kingdom of Morocco Between the challenges of the present and the stakes of the future Dr.Louazi Abdelouahid,Dr. El-battioui Fadoua,Ms. Boukil Noura, Ms. BEN ALLAL Zohra 5. The impact of applying value-added tax on net profitability of financial services in Islamic banks in the Kingdom of Saudi Arabia Mr. Turki Saeed Al-Qahtani, Dr. Abdulrahman Saad Al-Qahtani 6. Testing the Kuznets curve hypothesis for the relationship between economic growth and environmental pollution in Sudan during the period 2000-2022 Co-Prof. Jaralnabi Babou Jaralnabi , Asst-Prof. Salma Nour Al-Huda Ahmed, Asst-Prof. Safia Omer Hapallah 7. Determinants of Small and Medium-Sized Enterprises’ Financing Demand in Saudi Arabia (1996-2020) Ms. Shrouq Saad Althobaiti, Asst-Prof. Nadia Ahmed Bajaber 8. Predicting The Inflation Rate in The Kingdom of Saudi Arabia Using Time Series Analysis From 2000 To 2023 Asst-Prof. Awaidia Mohammad Ismail